b n introduction to the Buddhist way of thought /c - Yeshe, Thubten (b, 1998)
This booklet offers the reproduction of three public lectures, including question and answer sessions, by Lama Yeshe on the general topic of Buddhism.
Keywords: Buddhism -- Psychology; Self-perception.; Self-help techniques